IDENTIFYING CUSTOMER BEHAVIOR IN HOSPITALITY TO DELIVER QUALITY SERVICE AND CUSTOMER SATISFACTION - Harnjo, Edward; Rudy, Rudy; Simamora, Javerson; Hutabarat, Linda Rotua; Juliana, Juliana (AGUSPATI Research Institute, 2021)
Hospitality is the largest and fastest growing industry in the world. The hospitality industry offers the best service and the best foods which provide in hotel. Many ways are done to increase the quality of service and food in hotel to get customer’s satisfaction. A hotel has many departments for its operational activities. One of them is Food and Beverage Department. Food and Beverage Department has important responsibility to maintain the quality of food and beverage service and product. Food and Beverage Department has many subdivisions that are responsible for maintaining the duties of each division. Consumer behavior is the decision-making process by consumers in selecting, buying, using, and taking advantage of product service or experience to satisfy consumers’ needs and desires. In this research, the author will discuss Customer Behavior at the Hotel JW Marriott Medan that aims to know more about customer characteristics and how to deal with them to give customer satisfaction. Based on the research, the authors also discussed about the regular guest who stayed in our hotel, about what they expect in five star hotels and how the staff look affect the perception of the hotel that in the end hotel to all these solutions that might be used as a input to the hotel. This research is expected to give a boost for hotel to resolve the problem and improve the quality of service the banquet aims to get customer satisfaction. The reader is expected to end this task can give information about the customers at JW Marriott Medan.. Keywords: Hospitality, quality service, customer satisfaction, customer behavior